2019
DOI: 10.20473/jfiki.v6i12019.17-24
|View full text |Cite
|
Sign up to set email alerts
|

Karakter Solid Lipid Nano Particle (SLN) – Ubiquinon (Q10) dengan Beda Jenis Kosurfaktan: Poloxamer 188, Lesitin, Propilen Glikol

Abstract: Pendahuluan: Ubiquinon atau Coenzyme Q10 (CoQ10) merupakan senyawa kimia yang tidak stabil terhadap cahaya, sehingga mudah terdegradasi. Oleh karena itu, sistem penghantaran yang bisa meningkatkan kestabilan dari CoQ10 sangat dibutuhkan. Solid lipid nanoparticles (SLN) diketahui mampu meningkatan stabilitas molekul, dan memiliki karakteristik pelepasan terkontrol. Karakteristik SLN (ukuran partikel dan efisiensi penjebakan obat), sangat dipengaruhi kompoen penyusun SLN. Tujuan: Tujuan dari penelitian ini adala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Besides that, it can produce small particle sizes because they have a smaller surface tension but concentration and technique for producing SLM need to be considered. [ 11 ] Melt o/w emulsification technique shows that quercetin SLM can be formulated as a dry powder which is suitable for the delivery of inhaled drugs, apart from that it is easier and can provide good entrapment results.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, it can produce small particle sizes because they have a smaller surface tension but concentration and technique for producing SLM need to be considered. [ 11 ] Melt o/w emulsification technique shows that quercetin SLM can be formulated as a dry powder which is suitable for the delivery of inhaled drugs, apart from that it is easier and can provide good entrapment results.…”
Section: Introductionmentioning
confidence: 99%
“…This is presumably because the HLB value is quite large, namely 29, so it works more effectively on the water phase which is the outer phase of the system. Particles surrounded by poloxamer 188 become more difficult to combine with each other, so the system becomes more stable [4]. With the advancement of science and technology, there are many methods that can be used to increase solubility, one of which is nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…(3) total weight of SLM powder where W total active is total amount of AA added to the system, W free active is the analyzed amount of free active. The values were averaged on three determinations (Jaspart et al, 2005;Rahimpour et al, 2016;Rosita et al, 2019).…”
Section: Entrapment Efficiency and Active Loadingmentioning
confidence: 99%
“…This may be because poloxamer 188 can effectively reduce the surface tension between the lipid phase and the aqueous phase during emulsification, resulting in a spherical particle shape. Moreover, the steric effect of poloxamer 188 could prevent a droplet agglomeration (Hariyadi et al, 2022;Rosita et al, 2019), hence the AASLMs stabilized by poloxamer 188 showed comparable particle shape before and after freezedrying. Our results were consistent with the study of Hariya (2022) which demonstrated that SLMs made of glyceryl behenate with poloxamer 188, to deliver quercetin, had a spherical morphology (Hariyadi et al, 2022).…”
Section: Powder Appearancementioning
confidence: 99%